Régimen Económico Matrimonial en el Derecho Español - Gonsálvez, Carmen Mingorance; Martins, Claúdia Sofia Antunes (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2015)
In the present work we will analize the economic effects of marriage in the spanish legal system. We will try to identify the different types of property regimes tipify in the law and its main characteristics, and the possibility of the spouses to choose other rules to disciplinate their marriage.